Privasi Dalam Bersosial Media - Dicky Wahyudi; Meyling Meyling; Muhammad Nawawi; Ryo Arya Esya Setiawan; Sevhia Khoirun Nisa; Siti Maulida Zahra; Aflah Ariyandi Haj Aflah (CV. Multi Kreasi Media, 2023)
In 2022, Indonesia has reached 191 million social media users, and this data has increased by 12.35% compared to the previous year which was only around 170 million. However, even without data like this, maybe all of us are already aware that the role of social media is very much needed in this all-digital era. This can be seen since two years ago when the whole world was hit by the Covid-19 disaster which required all of us to stay silent in our respective homes and do our activities or communicate only using social media. From this, social media is often used for the purposes of socializing, getting information, and looking for entertainment. The human desire to build communication through social media in a personal and private way is always there (Trepte & Reinecke, 2011). With social media, users get satisfaction from the process of disclosing themselves to the public they choose as contacts connected in their social network. At the same time, the more they disclose themselves on social media, the greater the risk of privacy violations. Alan Westin stated that privacy is a way that people do to protect themselves by temporarily limiting other people's access to them (Margulis, 2011). In other words, the issue of privacy is a matter of someone's protection and control over themselves. With the socialization of privacy in social media which was attended by SMK students, it is hoped that it will increase the participants' understanding of what is not permitted to be disseminated to the general public as a wise social media user so they can understand that privacy in social media is an important thing that must be considered. and minimize the negative impact of social media.